CASCADE, neutron detectors for highest count rates in combination with ASIC/FPGA based readout electronics - Klein, Martin; Schmidt, Christian Joachim (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2011)
The CASCADE detector system described herein is designed for high intensity neutron applications with high demands on the dynamical range, contrast as well as background. The detector front-end is a hybrid, solid converter gas detector using several gas electron multiplier (GEM) foils as charge transparent substrates to carry solid 10B layers. These coated GEMs are then stacked (“cascaded”) one behind the other to cumulate the detection efficiency of every layer without loosing position information. The use of GEM foils allows high count rates up to 107n/cm2s. The well-defined neutron absorption locus inside the thin boron layer provides sub-microsecond absolute time resolution, which opens the door towards new TOF applications. Because 96% isotopically enriched boron is available in large quantities in contrast to 3He, 10B-converter based neutron detector technology is one of the very few technological alternatives to 3He in view of the imminent crisis in world-wide supply of 3He. Using GEM foils, the neutron detection bottleneck shifts to data read-out electronics and its bandwidth. The CASCADE detector uses an ASIC electronic front-end paired with an adaptable integrated FPGA data processing unit to provide high rate capacity and realtime event reconstruction.